2014
DOI: 10.1590/s0102-86502014000500010
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the efficacy of ureteroscopic lithotripsy and extracorporeal shock wave lithotripsy on ureteral calculi

Abstract: Compared to the ureteroscopic lithotripsy treatment, extracorporeal shock wave lithotripsy treatment provided a significantly lower post-treatment stone free rate, but it also obviously brought out less postoperative complications, shorter operation time and hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…Patients in the ESWL group achieved a 92.70% overall SFR with a 44.88% retreatment rate and an 11.02% auxiliary procedure rate [8]. In this study, the 1-month SFR in the ESWL group and URS group was 75.9% and 88.2%, which was in line with the previous ndings [16]. The residual calculi would serve as the infection source, which led to recurrence of calculi [9].…”
Section: Discussionsupporting
confidence: 84%
“…Patients in the ESWL group achieved a 92.70% overall SFR with a 44.88% retreatment rate and an 11.02% auxiliary procedure rate [8]. In this study, the 1-month SFR in the ESWL group and URS group was 75.9% and 88.2%, which was in line with the previous ndings [16]. The residual calculi would serve as the infection source, which led to recurrence of calculi [9].…”
Section: Discussionsupporting
confidence: 84%
“…They demonstrated that SWL showed a lower SFR (p < 0.001, RR 0.82, 95% CI 0.74-0.90), a higher repeat treatment rate (p = 0.004, RR 3.46, 95% CI 1.50 to 7.97), lower patient satisfaction (p = 0.02, RR 0.87, 95% CI 0.78-0.98), lower postoperative complications (p = 0.40, RR 0.63, 95% CI 0.48 to 0.83), and shorter operation times (p = 0.002, SMD −1.12, 95% CI −1.81-−0.43) and hospital stays (p = 0.004, SMD −1.71, 95% CI −2.88-−0.55) than URSL. However, the authors did not analyze by stone size [34].…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al studied a meta-analysis of the efficacy of URSL and SWL on ureteral calculi. They enrolled 13 papers and reported a SFR, repeat treatment rate, patient satisfaction, postoperative complications, operation time, and hospital stays [34]. They demonstrated that SWL showed a lower SFR (p < 0.001, RR 0.82, 95% CI 0.74-0.90), a higher repeat treatment rate (p = 0.004, RR 3.46, 95% CI 1.50 to 7.97), lower patient satisfaction (p = 0.02, RR 0.87, 95% CI 0.78-0.98), lower postoperative complications (p = 0.40, RR 0.63, 95% CI 0.48 to 0.83), and shorter operation times (p = 0.002, SMD −1.12, 95% CI −1.81-−0.43) and hospital stays (p = 0.004, SMD −1.71, 95% CI −2.88-−0.55) than URSL.…”
Section: Discussionmentioning
confidence: 99%
“…En la búsqueda sistemática se encontró dos revisiones sistemáticas, de las cuales se seleccionó la RS de Xu (43) para los desenlaces de tasa libre cálculo, tasa de complicaciones y retratamiento.…”
Section: Pregunta 5: En Pacientes Con Litiasis Ureteral No Proximal unclassified